Synthesis, characterization and crystal structure of the cis-[RhL2Cl2]Cl complex with the bifunctional ligand (L) 2-(2′-pyridyl)quinoxaline. Biological activity towards PAF (Platelet Activating Factor) induced platelet aggregation - Philippopoulos, A.I.; Tsantila, N.; Demopoulos, C.A.; Raptopoulou, C.P.; V. Likodimos; P. Falaras (Polyhedron, 2009)
The reaction of RhCl3·3H2O with the ligand L = 2-(2′-pyridyl)quinoxaline (pqo) in a 1:2 molar ratio formed the mononuclear complex cis-[RhL2Cl2]Cl (1), which has been characterized by elemental analysis, FT-IR, FT-Raman, 1H, 13C NMR, electronic absorption spectroscopy and by electrospray mass spectrometry. The molecular structure of 1 (needle like and prismatic polymorphs) in the crystal has been elucidated by single-crystal X-ray diffraction, revealing a bidentate behavior of L, while the geometry around the Rh(III) atom is that of a distorted octahedron.. Preliminary biological tests revealed that this compound inhibited PAF-induced rabbit platelet aggregation. © 2009 Elsevier Ltd. All rights reserved.